Caracterização mineralógica por difração de raios X e determinação de terras raras por ICP-MS de rochas da região sul da Bahia - Amanda Luzia da Silva (2013)
This research concerns the relationship between the mineralogical composition and the abundance of rare earths in rocks of southern Bahia, using the method of X-Ray Diffraction (XRD) for mineralogical characterization and results of the determination of rare earth of the samples by ICP-MS. The mineralogical characterization by XRD made possible to identify only the major, and not the accessory minerals in most of the samples. The mineral separation by Frantz magnetic separator proved efficient for the identification of accessory mineralsby XRD and for characterization of samples which have many mineral phases, which causes excessive number of peaks in diffraction patterns.Results of mineralogical composition by optical microscopy showed the accessory minerals which not had been identified by XRD and also confirmed the results obtained by XRD to the major minerals. It was possible to perform the mineralogical characterization of the rocks by XRD method, however, it did not prove to be the most suitable method for analyzing materials that have many phases to be identified - as rocks because excessive number of peaks in diffraction patterns may cause overlapping of peaks and induce erroneous identifications.About Rare Earths Elements (REE), more than 50% of the samples showed high concentrations of light REE (LREE) in relation to the crust of the Earth and most of them had accessory minerals in their composition. All samples which had in their mineralogical compositions the accessory minerals: allanite, zircon, minerals of apatite and garnet groups show LREE enrichment, which suggests that these minerals may be responsible for the elevated levels of LREE in the whole- rocks